Risk Assessment, Risk Identification, and Control in The Process Of Steel Smelting Using the Hiradc Method - Rahardja, Untung (Pandawan, 2023)
Workplace accidents include illnesses brought on by working conditions, accidents on the way to and from work,and other incidents. Steel smelting, an operation that involves melting steel to produce an iron rod (billet), which issubsequently molded into different materials needed, is one of the work environments where accidents can happenwith risks ranging from low to severe. Using the HIRADC approach, work safety can undoubtedly be evaluated.Using a scale based on the potential outcome, this method can identify the risks, dangers, and assessments that mayarise throughout the steel-smelting process. The HIRADC approach will be used in this study to identify risks andgauge the likelihood of accidents in the Indonesian steel smelting process. As a result, 36 dangers with varyinglevels of low, medium, and high risk exist. Various additional safety tools must be owned because Indonesia's levelof safety control is still quite poor